An Empirical Study on the Perception of Undergraduate Students about the Challenges of the Current Education System and their Relation with the Communication Skills of the Students (International Journal of Food and Nutritional Sciences, 2022)
The performance indicator generally used to determine the value of higher education by the governments and international rankings is the employment rate of the graduates. The India Skills Report (ISR) 2022 explores skill building for the future of work in 2022 and beyond. Exploratory, descriptive and inferential research was conducted to study the perception of undergraduate students about the challenges of the current education system and their relation with the communication skills of the students. Quantitative and qualitative analyses have been used in the study. The primary data was collected from 250 respondents through a structured questionnaire. For hypotheses testing, Kendall’s Tau Correlation test and Spearman’s Rank correlation test were used in the study. The study concludes that there is a significant positive correlation between communication skills and the four challenges of the education system, viz. Teaching methodology, Educational Framework, Practical Exposure and Access to Resources. The qualitative analysis reveals that the gap between the current state of learning outcomes and what is required must be bridged by undertaking major reforms. The National Education Policy 2020 proposes the revision and heads forward to create a new system that is aligned with the aspirational goals of 21st-century education, including Sustainable Development Goal 4, while building upon India’s traditions and value systems.